2019
DOI: 10.1038/s41598-018-37937-1
|View full text |Cite
|
Sign up to set email alerts
|

Methylglyoxal down-regulates the expression of cell cycle associated genes and activates the p53 pathway in human umbilical vein endothelial cells

Abstract: Although methylglyoxal (MGO) has emerged as key mediator of diabetic microvascular complications, the influence of MGO on the vascular transcriptome has not thoroughly been assessed. Since diabetes is associated with low grade inflammation causing sustained nuclear factor-kappa B (NF-κB) activation, the current study addressed 1) to what extent MGO changes the transcriptome of human umbilical vein endothelial cells (HUVECs) exposed to an inflammatory milieu, 2) what are the dominant pathways by which these cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 72 publications
5
30
0
Order By: Relevance
“…This upregulation of nuclear phospho-p53 seems not accompanied with an increase in apoptosis rate but will likely activate p53 dependent signaling pathways. This would fit with recently published data showing an activation of the p53 pathway upon MGO treatment in human umbilical vein endothelial cells (HUVECs) [31]. Moreover, it was shown that the total amount of nuclear p53 is increased in hepatocellular carcinoma cells upon MGO treatment.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…This upregulation of nuclear phospho-p53 seems not accompanied with an increase in apoptosis rate but will likely activate p53 dependent signaling pathways. This would fit with recently published data showing an activation of the p53 pathway upon MGO treatment in human umbilical vein endothelial cells (HUVECs) [31]. Moreover, it was shown that the total amount of nuclear p53 is increased in hepatocellular carcinoma cells upon MGO treatment.…”
Section: Resultssupporting
confidence: 90%
“…In cell culture model systems often near toxic concentrations of MGO ranging from 50 µM up to 2 mM MGO are applied. For instance, HUVEC cells were treated with up to 800 µM MGO to copy injuries in endothelial cells typically seen in diabetes patients knowing that these concentrations do not reflect the plasma concentrations of MGO even in diabetes patients [31]. The authors argued that the in vivo situation is rather a complex mixture of compounds acting in synergy than a single compound leading to this phenotype [31].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A glutathione peak and a putative methylglyoxal peak were also detected in these samples (Figure 3d), and were also somewhat more abundant in G1. These results suggest that methylglyoxal metabolism may be cell-cycle associated, consistent with reports that methylglyoxal treatment of cells can cause cell cycle arrest (37)(38)(39).…”
Section: Identification Of Lactoylglutathione a Novel Cell-cycle Asssupporting
confidence: 91%
“…In this context it would be also important to know, how MGO or glycation alter the expression of polysialyltransferases. Although recent studies demonstrate that MGO alters gene expression profiles [24], the mechanism how MGO interfere with transcription is still unknown. It is conceivable that glycation of transcription factors is the major cause for this observation.…”
Section: Discussionmentioning
confidence: 99%